Molecular Characterization Based on Whole-Genome Sequencing of Streptococcus pneumoniae in Children Living in Southwest China During 2017-2019 - Yan, Ziyi; Cui, Yali; Huang, Xiaocui; Lei, Shikun; Zhou, Wei; Tong, Wen; Chen, Wen; Shen, Meijing; Wu, Kaifeng; Jiang, Yongmei (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Streptococcus pneumoniae is an important pathogen causing high morbidity and high mortality in children and undergoes frequent recombination for capsule switching to neutralize the 13-valent pneumococcal conjugate vaccine (PCV13). This study aimed to investigate the prevalence, and molecular characteristics including serotypes and antibiotic susceptibility of S. pneumoniae isolated from children living in Southwest China to facilitate the selection of effective vaccine formulations and appropriate antibiotic treatment regimens. Methods: This study was conducted at West China Second University Hospital (Chengdu, Sichuan Province, China), Zunyi Medical University Third Affiliated Hospital/First People's Hospital of Zunyi (Zunyi, Guizhou Province, China) and Chengdu Jinjiang District Maternal and Child Healthcare Hospital (Chengdu, Sichuan Province, China). Demographic and clinical characteristics of children infected with S. pneumoniae were collected and analysed. Next-generation sequencing and sequence analysis were used to determine the serotypes, sequence types, antibiotic resistance and potential protein vaccine target genes of the pneumococcal isolates. The coverage rate provided by PCV13 was estimated by calculating the percentage of the specific serotypes that were specifically the PCV13-included serotypes. Antimicrobial susceptibility was determined by the microdilution broth method. Results: The most prevalent pneumococcal serotypes were 19F (25.8%), 19A (14.1%), 6B (12.5%), 6A (9.4%) and 14 (7.8%). The predominant STs were ST271 (23.3%), ST320 (15.5%) and ST90 (8.6%), dominated by the clonal complex Taiwan19F-14 (39.1%). The coverage rate of PCV13 was 77.3% in all the isolates, with relatively higher values in invasive isolates (86.4%). Over the decade, the rates of resistance to penicillin, amoxicillin and cefotaxime were 5.6%, 5.3% and 5.1%, respectively, with significantly higher values in invasive isolates (22.4%, 14.9% and 11.9%). Almost all the isolates were resistant to erythromycin (99.1%) and clindamycin (95.9%). All isolates carried virulence-related genes, including ply, psaA, piaA, piuA, phtE, nanA, pepO, danJ, pvaA, clpP, pcsB and strH. The carriage of virulence and resistance genes varied among serotypes and clades, with serotype 19F/ST271 showing higher resistance to antibiotics and being more likely to carry pilus genes and other virulence genes. Conclusion: These data provide valuable information for the understanding of pneumococcal pathogenesis, antimicrobial resistance and the development of protein-based vaccines against pneumococcal infection.